HADITH AND THE ETHICS OF PUBLIC SPACE: the Case of the Sea Fence Conflict in Tangerang - Saputra, Ilman Hendrawan (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2025)
The construction of a sea fence along the coast of Tangerang Regency has sparked complex legal, social, and religious controversies. This study critically examines the legal status of the project and its socio-economic implications for coastal communities through the lens of prophetic hadiths and Indonesian agrarian law. Employing a multidisciplinary methodology, the research integrates spatial analysis using historical Google Earth imagery (1985–2024), linear regression modeling for shoreline change estimation, normative analysis of regulations such as Government Regulation No. 24/1997 and Ministry of Agrarian and Spatial Planning Regulation No. 17/2021, and a textual analysis of relevant ṣaḥīḥ hadiths. The findings reveal systemic administrative irregularities involving land document falsification and abuse of authority, which contravene both Indonesian law and prophetic ethical teachings. Key hadiths—such as